Hemorrhagik Sindrome in Chronik Diffuze Liver Diseases (Eurasian Medical Research Periodical, 2023)
The main signs of hemorrhagic syndrome in chronic hepatitis and liver cirrhosis with viral etiology were divided into the nosebleeds in 32.76%, gums bleeding in 27.59%, skin petechia in 25.0%, hemorrhoidal bleeding in 19.83%, bleeding from varicose veins of the esophagus in 18.96%, menorrhage in 17.24% and bleeding from the gastrointestinal tract in 16.38% of patients. Hemorrhagic syndrome was expressed in cirrhosis of the liver HBV and HBV + HDV etiology 57.14% and 62.50%, respectively, to a lesser extent with cirrhosis of the liver HCV etiology 34.78%, but in liver cirrhosis of non-viral etiology hemorrhagic syndrome was detected in 25% of cases. In chronic viral hepatitis HBV and HCV etiology hemorrhagic syndrome was 11.76% and 5.26%, respectively, which indicated a lesser violation of the hemostasis system than in liver cirrhosis with viral etiology. As soon as there is a pronounced hemorrhagic syndrome in liver cirrhosis with viral etiology, a detailed study of coagulation and vascular platelet hemostasis is required to prevent and treat bleeding syndrome